Composition, density and distribution of Tomopteridae, Polychaeta, in the Costa Rica Thermal Dome, Eastern Tropical Pacific. - Fernández-Álamo, María Ana (2020)
Introduction: The tomopterids are holopelagic polychaetes widely distributed in all oceans, nevertheless they have been poorly studied despite their important implications in the trophic webs, as predators of various groups of zooplankton, including eggs and fish larvae. Objective: To describe the structure of the community of these pelagic worms in an upwelling area in the Central American Pacific. Methods: The zooplankton samples were obtained during the oceanographic campaign DOMO IV organized by the Universidad Nacional Autónoma de Mexico, in July-August, 1982. The polychaetes of the Tomopteridae family were sorted out and identified providing data on their specific composition, abundance and distribution. Results: Four species of the genus Tomopteris were determined, being T. elegans and T. planktonis dominant, T. nationalis constant and T. euchaeta rare. T. nationalis, T. elegans and T. euchaeta have tropical and subtropical affinies, while T. planktonis have been considered as cosmopolitan species. T. elegans had the higher relative abundance (62%) and T. euchaeta the lower (2.5%). Conclusion: Overall, T. elegans and T. planktonis showed a notable rise in the abundance related to upwelling in the thermal dome of Costa Rica.